SALMONELLA IN THE FEED INDUSTRY: PROBLEMS AND POTENTIAL SOLUTIONS - Zorica Tomičić; Ivana Čabarkapa; Radmilo Čolović; Olivera Đuragić; Ružica Tomičić (Journal of Agronomy, Technology and Engineering Management, 2019)
Salmonella is one of the most important foodborne zoonotic pathogens, with significant health and economic impact in both humans and animals. The control of Salmonella in animal feedstuffs is important, principally to protect the human food chain from contamination by Salmonella derived from infected animals. Salmonella can reach into the animal feed by multiple ways and during all production stages. Main sources of contamination are fertilizers on the pasture/fields, ingredients, co-products, dust, wild animals and contaminated equipment. Thus, there is importance for implementation of strategies for preventing feed contamination with Salmonella, by minimizing dust, maximizing hygiene of space and processing equipment in feed mills and implementing control measures in each stage of feed production. Elimination of Salmonella refers to thermal treatment (pelleting, extrusion) or chemical treatment. Feed additives, such as organic acids, short- and medium-chain fatty acids, prebiotics, probiotics and, more recently, essential oils of plant origin, have the potential to reduce Salmonella levels when added to the feed. Therefore, the purpose of this review is to discuss the prevalence and prevention methods for the control of Salmonella in the feed industry.